Diversity of Mesofauna and Macrofauna of Soil at Tin Post-Mined Area in Belitung Residence, Province of Bangka-Belitung - Iwan Hilwan; Eko Putranti Handayani (Jurnal Silvikultur Tropika, 2013)
The existence of mesofauna and macrofauna of soil depend on availability of energy and feed resources for sustainable their life, such as organic matter and biomass which is related with carbon cycle in the soil. Availability of energy and nutrient for soilfauna, could be growth and their activities will be in good perform and give positif impact to soil fertility. The obyective this study to identify species diversity of mesofauna and macrofauna of soil and to analyse environment factors which is influence on availability of mesofauna and macrofauna of soil at several ages tin post-mined area in Belitung Residence. The benefit this research to provide information and suggestion  to monitor diversity of mesofauna and macrofauna of soil at tin post-mined area and environmental changes in physical and chemical soil properties, with the result that can determine next treatments for reclamation activity in tin post-mined area. The result showed that the age of tin post-mined area is very important  factor to influence of species diversity level of mesofauna and macrofauna of soil. This factor is direct related with development of vegetation and dynamic of physical and chemical soil properties. Sample plot in Batu Itam village with vegetation like secondary forest have highest value of richness index and heteroginity index than sample plot in Aik Merbau village and Tanjung Pendam village which is vegetation as shrub.